FAMILY COMMUNICATION PATTERNS IN EDUCATING ELEMENTARY SCHOOL-AGE CHILDREN WITH RELIGIOUS CHARACTER IN THE NORTHERN HAMLET OF DADAPAN RIVER GRUJUGAN BONDOWOSO - Sugiarto, Achmad Bagus (Tsaqofah : Jurnal Pendidikan Islam, 2021)
Parents are the first and main educators for their children. Because parents are the first to carry out educational activities to provide positive and negative influences, even from the womb. As equal colleagues, mothers and fathers should be polite to their children. One of the desires and ideals of every parent is that children can be educated so that they have a religious character. So that children not only believe in the supernatural and carry out worship, but appear in their overall behavior as a whole virtuous human being (morally good), based on belief or faith in God and personal responsibility in the next day.One of the things that is very important in educating children is communication. Parents should be able to build a good and appropriate communication in educating and interacting with children. Keywords: family communication, child education, religious character